ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA PEMERINTAH DAERAH KABUPATEN ROKAN HULU - Nurhayati (Jurnal Ilmiah Cano Ekonomos, 2015)
This study aims to provide information to the public regarding the presentation of thegoverment’s performance in achieving accountability. To determine the performance of RokanHuludistrict goverments using financial ratios budget especially the ratio of local independence, the ratiothe area of financial dependence, the ratio of effectiveness, efficiency ratio, the ratio of the ratio ofthe activity, the ratio of growth. Financial ratio analysis on revenue and expenditure budget for the2009-2012 fiscal yaer as measured by ratio of local independence is very low, the ratio the area offinancial dependence is very high, the ratio effectiveness of the fiscal year 2009-2012 is very effectivewhile the effeciency ratio of the fiscal year 2009-2012 is very efficient, the ratio of the activity of thefiscal 2009-2012 which explains that the results routine spending is prioritized ratio compared to theratio of development expenditure,and ratio of growth to ain increase in local revenues that fluctuatefrom year 2009-2012.